The Influence of Content Quality And Price On Purchase Decision of Skintific Skincare Products Mediated By Visibility Celebrity Endorsers (Empirical Study: Instagram Users In Jakarta) - Margaretta Sianturi, Ristyna Lidya; Bambang Sugiyanto, Liem (Asian Journal of Social and Humanities, 2024)
The aim of this research is to analyze more deeply the relationship and influence of content quality, price on purchase decisions mediated by celebrity endorsers on purchase decisions via Instagram. The method used in this research is a quantitative method. In this research the variables used are independent variables, mediating variables and dependent variables. The independent variables used are price and content quality. The mediating variable used is Celebrity endorser. The Dependent variable used is Purchase decision. The population in this study are Instagram social media account users who live in Jakarta with a sample size of 150. Data analysis techniques using SEM with AMOS tools. The conclusions are Price influences Celebrity Endorser, Celebrity Endorser influences Purchase decisions, Price influences purchase decisions, and Price influences purchase decisions through celebrity endorsers with a CR value of 2.06 > 1.96